Pengaruh Teamwork Terhadap Kinerja Karyawan Pada Perusahaan - Putri Wulansari; Anniez Rachmawati Musslifah (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
This research discusses the importance of teamwork in improving employee performance in a company. Teamwork is an effective way to unite all employees in achieving company goals with better results. Several important aspects of teamwork include clear goals, open and honest communication, cooperative decision making, and an atmosphere of trust. Research shows that teamwork has a positive influence on employee performance, especially in teams involved in complex knowledge work. Other factors that influence employee performance include competence, work motivation, leadership, and work environment. Employee performance assessments are carried out to improve work quality, career development and compensation adjustments. This research uses qualitative methods with literature studies to explore information from various relevant sources.